Implementation and staff perceptions of a quality assurance system in a Finnish private hospital during the COVID-19 Pandemic: A qualitative study - Mira Huusko; Anni Vuohijoki; Leena Ristolainen; Juhana Leppilahti; Sanna-Maria Kivivuori; Heikki Hurri (PLoS ONE, 2025)
Background Implementing quality assurance systems in healthcare settings is a growing trend globally. However, the impact of such systems on staff well-being and patient safety, particularly during major disruptions such as the COVID-19 pandemic, remains insufficiently explored. This study investigates how the implementation of the Joint Commission International (JCI) accreditation system affected a Finnish private hospital during a period of organisational change and crisis. Methods This qualitative study was conducted through seven focus group interviews in two rounds (2020 and 2022) with a total of 27 healthcare professionals. The participants represented various professional groups in the hospital. Data were analysed using conventional qualitative content analysis to identify themes related to staff experiences, perceived benefits, and challenges associated with the quality assurance system. Results The implementation of the quality assurance system was initially viewed positively, especially for its potential to unify guidelines, support staff orientation, and improve patient safety. However, the process was perceived as time-consuming and misaligned with local practices. The COVID-19 pandemic and changes in hospital ownership significantly slowed implementation. Despite this, the system was considered beneficial for institutional credibility, marketing, and internal clarity of roles and responsibilities. Conclusions While comprehensive quality assurance systems such as JCI can enhance process transparency and patient outcomes, their successful integration requires contextual adaptation, dedicated resources, and sustained leadership. Staff well-being and participation should be prioritized throughout the process to ensure long-term benefits.